ANALYSIS OF FACTORS CAUSING CONVENTIONAL BANK CUSTOMERS TO TAKE OVER TO SHARIA PEOPLE'S FINANCING BANKS(CASE STUDY OF PT BANK FINANCING RAKYAT SYARIAH SUNGAI PUA) - Nisa Andriyani; Zuwardi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
The research carried out by the author was motivated by the existence of customers who paid off their debts and took over to sharia people's financing banks because sharia people's financing banks applied smaller margin limits in carrying out financing so that the installments charged to customers were also small, the interest in conventional banks was not stable makes customer financing installments uncertain. The aim of this thesis is to identify and analyze the factors that cause conventional bank customers to take over to PT Sungai Pua sharia people's financing bank. The method used in this research is qualitative procedures, which produce descriptive data with information from institutions involved in the research object. The factors that cause conventional bank customers to take over to the Sungai Pua sharia people's financing bank are divided into two, namely internal factors and external factors. Internal factors are easy requirements, easy installments and increasing bank income. External factors are the customer's desire to carry out sharia-based financing, fluctuations in interest rates, less than optimal services, persuasion from friends and friends and to get fresh money.